2010
DOI: 10.1002/bip.21508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2‐hydroxypropyl‐β‐cyclodextrin on thermal stability and aggregation of glycogen phosphorylase b from rabbit skeletal muscle

Abstract: The study of the kinetics of thermal aggregation of glycogen phosphorylase b (Phb) from rabbit skeletal muscles by dynamic light scattering at 48°C showed that 2-hydroxypropyl-β-cyclodextrin (HP-β-CD) accelerated the aggregation process and induced the formation of the larger protein aggregates. The reason of the accelerating effect of HP-β-CD is destabilization of the protein molecule under action of HP-β-CD. This conclusion was supported by the data on differential scanning calorimetry and the kinetic data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Thus we infer that the formation of the start aggregates proceeds on the all-or-none principle. This pattern was demonstrated for thermal aggregation of β L -crystallin from bovine lens [12], [37], GAPDH from rabbit skeletal muscle [6], [23], [35], [37], [43], yeast alcohol dehydrogenase I [26], [37], tobacco mosaic virus coat protein [37], [44], Ph b from rabbit skeletal muscle [5], [23], [29], [37], [43], [45], aspartate aminotransferase from pig heart mitochondria [46] and creatine kinase from rabbit skeletal muscle [7]. On the basis of these experimental data a new model of protein aggregation was proposed [12], [23], [36], [37].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Thus we infer that the formation of the start aggregates proceeds on the all-or-none principle. This pattern was demonstrated for thermal aggregation of β L -crystallin from bovine lens [12], [37], GAPDH from rabbit skeletal muscle [6], [23], [35], [37], [43], yeast alcohol dehydrogenase I [26], [37], tobacco mosaic virus coat protein [37], [44], Ph b from rabbit skeletal muscle [5], [23], [29], [37], [43], [45], aspartate aminotransferase from pig heart mitochondria [46] and creatine kinase from rabbit skeletal muscle [7]. On the basis of these experimental data a new model of protein aggregation was proposed [12], [23], [36], [37].…”
Section: Resultsmentioning
confidence: 84%
“…Our investigations have shown that Ph b is a convenient model for testing the compounds affecting protein denaturation and aggregation [4], [5], [25], [29], [45], [57]–[60]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) for the description of the initial parts of the kinetic curves of protein aggregation was demonstrated for thermal denaturation of Ph b [50], [76], [78], [79], GAPDH [80][82] and creatine kinase (CK) [83]from rabbit skeletal muscles and DTT-induced aggregation of α-lactalbumin [18] and insulin [84]. The practical significance of Eqs.…”
Section: Theory Quantification Of the Chaperone-like Activitymentioning
confidence: 99%
“…Among the suggested strategies to create artificial chaperones, on can mention the use polysaccharide gels [1,2], detergents [3] or polymeric micelles [4,5] with following action of cyclodextrins, as well as cyclodextrins themselves [6]. These approaches are very promising though cyclodextrin itself can affect the proteins [7,8]. Another way is the use of liposomes [9].…”
Section: Introductionmentioning
confidence: 99%